The Role of Islamic Education with Insight of Multicultural Values to Realize Harmony Between Students in Diversity (Case Study at SMA Negeri 2 Sigi, Sigi Regency, Central Sulawesi) - Rizka Fadliah Nur; Taufik Eka Riandhana (dialektika kontemporer, 2022)
Indonesia is a pluralistic country consisting of various ethnic groups, religions and races, so it is vulnerable to frictions of differences that can ignite divisions in the social life of the nation and state. Based on this, inter-religious harmony in Indonesia needs to be cared for and maintained, this is based on the many cases of violence involving religious factors. The principles of tolerance in religious life will be implemented if a Muslim gives freedom to embrace religion according to his beliefs and beliefs. The number of social media that is currently developing can make it easier to communicate and convey information, so that the information currently developing on social media is sometimes without any filtering so that a lot of hoax or untruthful information can trigger public misunderstandings which consequently can lead to things that are not true. negative thing. Problems that are often found and occur in education circles in high school include: (1) Fights between students often occur in schools. (2) Bullying between students is still common, either by physical or non-physical contact. (3) There is still discrimination in schools in terms of race, ethnicity, language, culture and religion. (4) Forming gangs among students that have a negative impact on themselves, the school and the local environment. Basis This research was conducted using survey research methods, namely research that took samples from one population and used a questionnaire as the main data collection tool. The results of the study, SMA Negeri 2 Sigi is a multicultural school with so much diversity in it, because in this school various religions, races, ethnicities, cultures, gather here, with a harmonious atmosphere of kinship. SMA Negeri 2 Sigi is not only a school to study, or produce students who excel, but character building here is seriously carried out. Various trainings that continue to be intense and consistent for students, do not be surprised if the diversity here goes well, because all school components are involved in it and synergize with each other so that the existing process goes well, then SMA Negeri 2 Sigi consistently has good character and achieve achievements in various fields. All the achievements obtained are inseparable from the good cooperation of the school and the harmony of all elements of society.